2013
DOI: 10.1186/1477-7525-11-164
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcome instruments used in clinical trials of HIV-infected adults on NNRTI-based therapy: a 10-year review

Abstract: BackgroundPatient-reported outcomes (PROs) may provide valuable information to clinicians and patients when choosing initial antiretroviral therapy.ObjectiveTo identify and classify PRO instruments used to measure treatment effects in clinical trials evaluating NNRTIs.MethodsWe conducted a structured literature review using PubMed to identify NNRTI trials published from March 2003 to February 2013. Studies identified--based on disease, instrument, PRO, and NNRTI medication terms were reviewed--to identify PRO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
0
34
0
3
Order By: Relevance
“…The use of PRO tools within these studies provides insight into patient-reported symptoms that may be underreported by individuals during standard screening for adverse drug events [ 38 ]. Others have suggested increasing the use of PRO tools in clinical research in order to differentiate in greater detail the benefit of various regimens [ 31 , 39 , 40 ]. Additionally, the use of longitudinal modeling allows for a greater understanding of the prevalence of HIV symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PRO tools within these studies provides insight into patient-reported symptoms that may be underreported by individuals during standard screening for adverse drug events [ 38 ]. Others have suggested increasing the use of PRO tools in clinical research in order to differentiate in greater detail the benefit of various regimens [ 31 , 39 , 40 ]. Additionally, the use of longitudinal modeling allows for a greater understanding of the prevalence of HIV symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-SI is a validated PRO instrument that assesses the burden of 20 common symptoms associated with HIV treatment or disease [ 30 ]. The instrument is considered to be the gold standard in contemporary HIV symptom research [ 31 ]. Respondents are asked about their experience with each of 20 symptoms during the past 4 weeks using a 5-point, Likert-type scale.…”
Section: Methodsmentioning
confidence: 99%
“…Although the differences in utility between various PRO tools used in HIV trials are not yet clear [ 22 ], it is increasingly recognized that the integration of PRO data into clinical practice (e.g. maintaining a database of PROs associated with individual ART regimens that also includes the degree of bother) would facilitate patient counseling and treatment optimization, and therefore improve patients’ QoL [ 22 24 ]. In addition, an accurate assessment of PROs could address the problem of underreporting certain AEs in clinical trials [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ma un aspetto tutt'oggi ancora da definire è quali siano vantaggi e svantaggi dei differenti strumenti di misurazione dei PRO in modo da costruire una batteria di strumenti che sia utilizzabile al meglio nei trial clinici. In una recente revisione sistematica di letteratura, si è valutato l'utilizzo dei PRO in trial clinici su NNRTI e si sono identificati 27 strumenti di valutazione (11). Tra essi, il Medical Outcomes Study HIV Health Survey (MOS-HIV) si è dimostrato il più comunemente utilizzato (8 trial).…”
Section: Patients Reported Outcomes: Istruzioni Per L'usounclassified
“…È il caso di strumenti di HRQL come il MOSHIV, il Functional Assessment of HIV Infection (FAHI) e WHOQOL-HIV BREF, che sono stati mutuati a partire da strumenti generici come SF-20, Functional Assessement of Cancer Therapy-General (FACT-G) e il WHOQOL-BREF, includendo considerazioni e aspetti che derivavano direttamente da pazienti con infezione da HIV o da medici che curavano i pazienti con infezione da HIV stessa. Gli autori sono generalmente concordi nel ritenere tali strumenti specifici per l'infezione da HIV molto utili in termini di misurazioni psicometriche nella popolazione HIV, mentre rivestono meno valore rispetto ai test generici laddove si voglia andare a includere tali misurazioni in valutazioni clinico-economiche tramite health technology assessment (11). Solo negli ultimi anni i trials clinici hanno previsto nel loro disegno originale un'analisi di valutazione dei PRO (12)(13)(14).…”
Section: Patients Reported Outcomes: Istruzioni Per L'usounclassified